At the End of an Era: A Model and Three Tales of Memory, Perception, and Reality - Tasselli, Stefano (Academy of Management Review, 2019)
The concept of ‘era’ and the study of the transition between eras have surfaced in organizational research across a various range of theories and topics. However, conceptual and methodological limitations have left unexplored the entrenchment between the holistic process of change and the socio-psychological patterns underlying the passage between an ending era and an upcoming one. In this essay, I develop a model that conceptualizes the end of an organizational era as the interplay between the epistemological elements of Memory and Perception and the ontological element of Reality. I review three cases, built from three novels, which take distinct conceptual patterns to explore how the connections between Memory, Perception and Reality help define and interpret organizational eras. Building on these three cases, I discuss the ways organizational scholars can disentangle the conceptual and practical issues associated with the change of an era, and ultimately learn how to organize and manage this change. KEYWORDS: Era; Memory; Perception; Reality; Organizational change; Organization theory.